2014
DOI: 10.1177/1352458514524293
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography and visual evoked potentials: which is more sensitive in multiple sclerosis?

Abstract: In eyes without ON, VEPs were more frequently abnormal than OCT, while the two techniques showed similar sensitivity in eyes previously affected by ON. The correlation of VEPs and OCT measures with disability prompts further exploration of the two techniques as potential markers of disease burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
44
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 30 publications
9
44
1
7
Order By: Relevance
“…12,13 Our VEP results are also similar to a prior study in which in 48 of the 85 (56%) pediatric patients with MS demonstrated VEP prolongation more than 2.5 SDs beyond control mean latencies and/or reduced amplitudes. 2 Also in line with our findings, another study of 14 pediatric patients with MS reported no difference in VEP latencies between MS-ON eyes and MS non-ON eyes ( p = 0.524) or between MS-ON eyes and MS fellow eyes ( p = 0.654).…”
Section: Discussionsupporting
confidence: 89%
“…12,13 Our VEP results are also similar to a prior study in which in 48 of the 85 (56%) pediatric patients with MS demonstrated VEP prolongation more than 2.5 SDs beyond control mean latencies and/or reduced amplitudes. 2 Also in line with our findings, another study of 14 pediatric patients with MS reported no difference in VEP latencies between MS-ON eyes and MS non-ON eyes ( p = 0.524) or between MS-ON eyes and MS fellow eyes ( p = 0.654).…”
Section: Discussionsupporting
confidence: 89%
“…There are studies that find both of these methods to be helpful for subclinical involvement detection (Trip et al, 2005;Fisher et al, 2006; Klistorner et al, 2008;Naismith et al, 2009;Talman et al, 2010). Our study showed significant correlation between RNFLT with mean VEP amplitude and latency, as previously observed (Naismith et al, 2009;Di Maggio et al, 2014). However, a few authors have described a relationship between RNFLT and P 100 latency, (Fatehi et al, 2012), and with N75/P 100 latency (Trip et al, 2005).…”
supporting
confidence: 81%
“…We found a significant positive correlation between RNFLT and mean N75/P100 amplitude in patients without ON (r s = 0.43; p < 0.001), and after ON (r s = 0.45; p < 0.001). Both in patients without p < 0.001) (Di Maggio et al 2014). Afferent visual pathways represent an acute demyelination episode through acute ON, while in the case of chronic, subclinical retinopathy and optic neuropathy -diffuse, chronic central nervous system damage.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Thus, any diagnostic model being developed should prioritize OCT measures as critical and visual function measures as enhancing the model. Based on previous studies that demonstrated RNFL thickness and visual evoked potentials (VEP) have similar sensitivities in optic neuritis eyes, it may be interesting to include VEP in a future diagnostic model with GCIP thickness and/or PMB thickness …”
Section: Discussionmentioning
confidence: 99%